Endoscopic surveillance of colorectal cancer in inflammatory bowel diseases: a review of the literature. Issue 10 (2nd October 2020) - Vitello, Alessandro; Shahini, Endrit; Macaluso, Fabio S.; Morreale, Gaetano C.; Sinagra, Emanuele; Pallio, Socrate; Maida, Marcello
ABSTRACT: Introduction: The risk of colorectal cancer (CRC) in patients with inflammatory bowel diseases (IBD) is higher compared to the general population and it is related to the type, severity, duration, and extension of the disease. Areas covered: This review aims to highlight current evidence from the literature supporting the role of endoscopic surveillance of CRC in patients with IBD. Expert opinion: Even in the absence of randomized controlled trials (RCTs), evidence from the literature supports the effectiveness of endoscopic surveillance in reducing IBD-related CRC incidence and mortality. As a consequence, current guidelines recommend colonoscopy 8–10 years after disease or symptom onset in all patients with ulcerative colitis (UC) and Crohn's disease (CD) involving at least one-third of the colon and agree on the necessity of annual surveillance in high-risk patients. Nevertheless, an overall agreement on the optimal intervals for surveillance of low-intermediate risk patients is absent and 2–5 year intervals have been proposed. In the near future, further studies are needed to assess the most effective intervals and tailor the surveillance based on the personal risk profile. Additionally, further efforts should be made to evaluate the role of noninvasive tests as primary screening, thus avoiding unnecessary colonoscopies.